â€œProaktif Teachersâ€ Training to Increase Emotional Regulation of Teachers in Vocational Schools - Yungsiana, Istiqomah; Martani, Wisjnu (Psikopedagogia, 2020)
Emotion regulation is an important aspect in teachers a teacherâ€™s everyday life. However, facts show that some teachers fail to properly regulate their emotions. Accordingly, an intervention is needed to enhance teachersâ€™ emotional regulation. â€œPROAKTIF Teachersâ€ is a training module developed to increase teachersâ€™ emotional regulation. The â€œPROAKTIF Teachersâ€ training was structured based on a â€œPROAKTIFâ€ Guidance and Counseling Model. This research aimed to find out the effect of â€œPROAKTIF Teachersâ€ training on vocational School teachersâ€™ emotional regulation. The research method was quasi experiment using the untreated control group design with dependent pretest and posttest samples. Twenty-six vocational school teachers participated in this study, they were assigned into experimental and control groups. The participants were recruited using purposive sampling technique.The research instruments were emotional regulation scale, â€œPROAKTIF Teachersâ€ module, and manipulation check. Data analysis used mixed annova. The result of the research showed that â€œPROAKTIF Teachersâ€ training did not have significant effect in increasing emotional regulation of teachers in Vocational schools. The result of the present study could be used as a reference to develop a training model to help vocational school teachers to improve their emotion regulation skills by considering several aspects found in the present study including duration, model, approach, theoretical basis, focus, and psychological values of the training.